Should the U.S. promote (illiberal) democracy in the Middle East? - Chin, John J. (Frontiers in Political Science, 2025)
This article reviews Shadi Hamid’s book The Problem of Democracy: America, the Middle East, and the Rise and Fall of an Idea. It interrogates three key assumptions behind the author’s call for abandoning a “stability first” strategy for a “democracy first” strategy in the Middle East. These include the claim that (1) liberalism and democracy are diverging, (2) Arab dictatorships are brittle, and (3) there is a stark tradeoff between prioritizing Arab-Israeli peace and Arab democracy.